2019
DOI: 10.3390/w11050928
|View full text |Cite
|
Sign up to set email alerts
|

Second Cheese Whey Treatment Using Zeolite under Continuous Flow Mode and Its Application on Wheat Growth

Abstract: The efficiency of natural zeolite to treat second cheese whey (SCW) and remove ammonium from artificial wastewater (AWW) was examined. Since zeolite has been reported to improve nitrogen availability in soils, its effect on wheat plant growth was also examined. Continuing a previous study using batch reactors, results are presented concerning experiments in fixed-bed columns under continuous operation. Results from the continuous flow column experiments using AWW and zeolite (2.0–2.8 mm) indicated that low flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Desorption experiments also showed that ammonium and organic matter were not easily released from zeolite, indicating the potential use of saturated zeolite for soil amendment. The follow-up study [9] included continuous flow column experiments, which also proved the ability of zeolite to adsorb nitrogen from second cheese whey, achieving an adsorption capacity of 15.30 mg NH 4 + -N/g. The saturated zeolite was used in plant growth experiments, which showed a positive effect of saturated zeolite on the plant production.…”
Section: Summary Of This Special Issuementioning
confidence: 94%
See 1 more Smart Citation
“…Desorption experiments also showed that ammonium and organic matter were not easily released from zeolite, indicating the potential use of saturated zeolite for soil amendment. The follow-up study [9] included continuous flow column experiments, which also proved the ability of zeolite to adsorb nitrogen from second cheese whey, achieving an adsorption capacity of 15.30 mg NH 4 + -N/g. The saturated zeolite was used in plant growth experiments, which showed a positive effect of saturated zeolite on the plant production.…”
Section: Summary Of This Special Issuementioning
confidence: 94%
“…A variety of agro-industrial wastewaters and treatment methods are presented in the papers discussed in this Special Issue. Two of the papers [8,9] focus on the use of natural zeolite in second cheese whey treatment, aiming to adsorb and recover nitrogen. The first paper [8] presented laboratory-scale experiments using artificial wastewater and second cheese whey.…”
Section: Summary Of This Special Issuementioning
confidence: 99%
“…Generally, whey proteins are highly valued and come in many different forms, such as whey powder (8-12% protein and over 70% lactose), WPC, containing between 30-89% of protein and WPI containing over 90% of protein and almost no lactose (around 3%). WPH contain about 80% of proteins that have been hydrolyzed by specific enzymes, being thus more easily metabolized and have nutraceutical properties [10,21,45].…”
Section: Whey Protein Concentrates (Wpc) Whey Protein Isolates (Wpi) and Whey Protein Hidrolyzates (Wph)mentioning
confidence: 99%
“…WPC production involves a final drying step which is carried out by spray or freeze drying. The cost of such equipment is high, which hampers their application in small/medium scale dairy industries [21].…”
Section: Whey Protein Concentrates (Wpc) Whey Protein Isolates (Wpi) and Whey Protein Hidrolyzates (Wph)mentioning
confidence: 99%
See 1 more Smart Citation